Faktor-faktor yang Berhubungan dengan Kesehatan Mental Ibu Hamil di Desa Pulau Rambai - Alini, Alini; Meisyalla, Langen Nidhana; Novrika, Bri (Jurnal Ners, 2024)
Pregnant women are a group that is vulnerable to mental health problems because of the changes they experience at various stages that affect their mental health. Nearly one in five pregnant women is affected by mental health problems during the pre-natal and postpartum periods. The mental health of pregnant women is very necessary during pregnancy. Good mental health not only affects pregnant women, but also the fetus in the womb. This research aims to determine the factors related to the health of pregnant women in Pulau Rambai Village, Kampa Health Center Working Area. The research design used was cross sectional. The population in this study is all pregnant women in Pulau Rambai Village, Kampa Community Health Center Working Area, with the sampling technique used is total sampling. Data analysis used univariate and bivariate analysis with the chi square test. Based on the research results, it is known that there is a relationship between age and the mental health status of pregnant women (Pv 0.000 ? 0.05), there is a relationship between education and the mental health status of pregnant women (Pv 0.000 ? 0.05), there is a relationship between parity and the mental health status of pregnant women ( Pv 0.000 ? 0.05), there is a relationship between knowledge and the mental health status of pregnant women (Pv 0.000 ? 0.05). It is hoped that pregnant women should be more aware of their own condition, more actively seeking mental health information both through health workers during ANC examinations and from other sources and media.